Winning startup competitions - TAN, Shao Yen (Institutional Knowledge at Singapore Management University, 2021)
Tan Shao Yen and Kush Agarwal were a mentor-mentee pairing in the Lee Kuan Yew Global Business Plan Competition. Their organisations are now collaborating to explore the application of new technology in the built environment